2008
DOI: 10.1136/vr.163.7.203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transplacental and contact transmission of bluetongue virus in cattle

Abstract: This paper presents evidence that a field strain of bluetongue virus serotype 8 (BTV-8) was transmitted transplacentally and that it was also spread by a direct contact route. Twenty pregnant heifers were imported from the Netherlands into Northern Ireland during the midge-free season. Tests before and after the animals were imported showed that eight of them had antibodies to bluetongue virus, but no viral RNA was detected in any of them by reverse transcriptase-PCR (RT-PCR). Two of the seropositive heifers g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 18 publications
3
128
0
4
Order By: Relevance
“…Four of the heifers then calved, and retesting a few days later showed that three calves and two antibodynegative heifers now tested positive by PCR, indicating recent infection. These results indicated that BTV transmission had been able to occur despite the apparent absence of an infection source and the lack of Culicoides vectors, as confirmed by a light trap operated throughout the period in the same building, and was the first indication that vertical and horizontal (oral) transmission of this strain might be possible (Menzies et al 2008), a finding that was supported by several subsequent studies (e.g. De Clerq et al…”
Section: -2005: Emergence Of Bluetongue Virus In Southern and Eassupporting
confidence: 75%
See 1 more Smart Citation
“…Four of the heifers then calved, and retesting a few days later showed that three calves and two antibodynegative heifers now tested positive by PCR, indicating recent infection. These results indicated that BTV transmission had been able to occur despite the apparent absence of an infection source and the lack of Culicoides vectors, as confirmed by a light trap operated throughout the period in the same building, and was the first indication that vertical and horizontal (oral) transmission of this strain might be possible (Menzies et al 2008), a finding that was supported by several subsequent studies (e.g. De Clerq et al…”
Section: -2005: Emergence Of Bluetongue Virus In Southern and Eassupporting
confidence: 75%
“…Although the secondary routes described above are likely to be of minor significance during normal transmission, they may become disproportionately important for the survival of the virus when normal transmission is interrupted by cold weather , and one or more of these mechanisms is likely to be responsible for the handful of BTV transmission events confirmed to have occurred during the winter in NW Europe (e.g. De Hoffmann et al 2008;Menzies et al 2008).…”
Section: Transmission and Ecology Of Bluetongue Virusmentioning
confidence: 99%
“…Documented transplacental infection and associated defects vary widely in sheep and cattle and is therefore unpredictable (Osburn, 1994;Maclachlan et al, 2000). Furthermore, in not all cases where animals were born either viraemic and/or PCR positive during the European outbreak of BTV-8 were nervous system lesions observed (De Clercq et al, 2008;Menzies et al, 2008;SantmanBerends et al, 2010;Saegerman et al, 2010). It is possible that neurological lesions may have become apparent if the infected foetuses were allowed to have developed to term.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency with which the BTV-8 strain was able to cross the placenta may have been a contributing factor that allowed the virus to persist during the adult vector free/low European winters. Several studies conducted in northwestern Europe have demonstrated the birth of seemingly healthy PCR positive and/or viraemic lambs or calves, some of which tested positive for viral RNA for several months (De Clercq et al, 2008;Menzies et al, 2008;Santman-Berends et al, 2010;Saegerman et al, 2010). These animals may have served as a source of virus for newly emerged adult midges in subsequent vector seasons.…”
Section: Several Characteristics Of the 2006-2008 Outbreak Of Btv-8 Imentioning
confidence: 99%
“…The virus is transmitted by specific species of Culicoides midges, family Ceratopogonidae (MacLachlan 1994). An evidence for transplacental and contact transmission of BTV was also described (Menzies et al 2008).…”
Section: Introductionmentioning
confidence: 99%